Evolution and regulation of developmental plasticity: body size and pigmentation in Drosophila - Lafuente, Elvira (2019)
"Phenotypic variation is a universal property of biological organisms and is the raw material for evolution by natural selection. Patterns of phenotypic variation in natural populations are greatly dependent on the external environment. Beyond filtering phenotypic variation in the process of natural selection, the environment can also play an instructive role leading to the production of phenotypic variants during development. Environmental cues, such as temperature or nutrition, can influence developmental rates and trajectories and lead to the production of different phenotypes from the same genotype; a phenomenon called developmental plasticity. In the wild, organisms are exposed to a variety of environmental cues that might affect the development of several traits in different manners.(...)"